2021
DOI: 10.3390/nu13072168
|View full text |Cite
|
Sign up to set email alerts
|

Usual Protein Intake Amount and Sources of Nursing Home Residents with (Risk of) Malnutrition and Effects of an Individualized Nutritional Intervention: An enable Study

Abstract: Nursing home (NH) residents with (risk of) malnutrition are at particular risk of low protein intake (PI). The aim of the present analysis was (1) to characterize usual PI (total amount/day (d) and meal, sources/d and meal) of NH residents with (risk of) malnutrition and (2) to evaluate the effects of an individualized nutritional intervention on usual PI. Forty residents (75% female, 85 ± 8 years) with (risk of) malnutrition and inadequate dietary intake received 6 weeks of usual care followed by 6 weeks of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…In this context, it is notable that in community-dwelling older adults, the prevalence of a protein intake below 0.8 g/kg BW/day is substantial (14–30%) and increases to 65–76% if a cut-off value of 1.2 g/kg BW/day is considered [ 35 , 36 ]. The situation seems to be even worse in nursing home residents, where a mean daily protein intake of only 0.7 g/kg BW has been reported [ 37 ]. Thus, the high risk of hip fractures in older adults, and particularly in nursing home residents, may, at least in part, be increased by a protein intake below the current recommendation.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is notable that in community-dwelling older adults, the prevalence of a protein intake below 0.8 g/kg BW/day is substantial (14–30%) and increases to 65–76% if a cut-off value of 1.2 g/kg BW/day is considered [ 35 , 36 ]. The situation seems to be even worse in nursing home residents, where a mean daily protein intake of only 0.7 g/kg BW has been reported [ 37 ]. Thus, the high risk of hip fractures in older adults, and particularly in nursing home residents, may, at least in part, be increased by a protein intake below the current recommendation.…”
Section: Discussionmentioning
confidence: 99%
“…Low blood urea nitrogen levels in elderly patients with CHD may be attributed to insufficient intake of protein-rich foods such as fish, meat and eggs, resulting in a negative nitrogen balance and reduced concentrations of blood urea nitrogen, a metabolite of protein. A large number of studies have confirmed that insufficient protein intake will lead to malnutrition ( 40 43 ). Meanwhile, a recent study showed that depression and malnutrition were found to be risk factors for adverse outcomes in patients with CHD ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present analysis, energy and protein intake from usual food sources as well as from supplementation did not change within the intervention phase (Table 2 ). In a secondary data analysis, limited to residents receiving a supplementation ( n = 40), we examined the effects of the intervention on protein intake in more detail and identified that the supplementation did not affect protein intake amount and sources from regular food components during the intervention phase compared to the usual care phase [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Usual nutritional care is described in detail in Supplement Fig. S1 and in previous publications [ 20 , 23 ]. Briefly, residents received three main meals (breakfast, lunch and dinner) and additional snacks, delivered from the central kitchen.…”
Section: Methodsmentioning
confidence: 99%